E-Pocket Book of Angiosperms Diversity of Ghimbo Pomuan Indigenous Forest to Improve Species Literacy and Plant Awareness of Students - Hidayah, Hikmah; Zubaidah, Siti; Setiowati, Frida Kunti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
Students' low species literacy and plant awareness towards plants are problems in learning biology, especially regarding local plant diversity. One alternative to overcome these problems is developing contextual learning media sourced from local plants. This study aims to develop and test the feasibility of e-pocket book media for Angiosperms diversity in Ghimbo Pomuan Indigenous Forest, Kampar, Riau, Indonesia, as an innovative solution for contextual and local wisdom-based taxonomy learning. The development of this e-pocket book uses the Lee & Owens multimedia development model with the stages of analysis, design, development, implementation, and evaluation. The validation results by material experts, media, and practitioners showed that the e-pocket book was classified as very valid, with an average score of 95.00% and 95.23%. The practicality test by students showed an average score of 9.00% in the convenience category. The effectiveness test showed an increase in species literacy and plant awareness in the experimental class with N-Gain values of 0.6621 and 0.6403, respectively, in the medium category, much higher than the control class. These results indicate that the e-pocket book improves species literacy and plant awareness. This media can support biology education that is contextual, relevant, and aligned with Sustainable Development Goal 15.